Optimal extent of surgical and pathologic lymph node evaluation for resected intrahepatic cholangiocarcinoma. Issue 5 (May 2018) - Brauer, David G.; Fields, Ryan C.; Tan, Benjamin R.; Doyle, M.B. Majella; Hammill, Chet W.; Hawkins, William G.; Colditz, Graham A.; Chapman, William C.
Abstract: Background: Lymph node (LN) status is an important predictor of overall survival for resected IHCC, yet guidelines for the extent of LN dissection are not evidence-based. We evaluated whether the number of LNs resected at the time of surgery is associated with overall survival for IHCC. Methods: Patients undergoing curative-intent (R0 or R1) resection for IHCC between 2004 and 2012 were identified within the US National Cancer Database. LN thresholds were evaluated using maximal chi-square testing and five-year overall survival was modeled using Kaplan–Meier and Cox regressions. Results: 57% (n = 1, 132) of 2, 000 patients had one or more LNs resected and pathologically examined. In the 631 patients undergoing R0 resection with pN0 disease, maximal chi-square testing identified ≥3 LNs as the threshold most closely associated with overall survival. Only 39% of resections reached this threshold. On multivariable survival analysis, no threshold of LNs was associated with overall survival, including ≥3 LNs (p = 0.186) and the current American Joint Committee on Cancer recommendation of ≥6 LNs (p = 0.318). Conclusion: In determining the extent of lymphadenectomy at the time of curative-intent resection for IHCC, surgeons should carefully consider the prognostic yield in the absence of overall survival benefit.